Ang Kok Siong - Siong, Ang Kok (2002)
Emotional intelligence has become increasingly popular since it enhances effective leadership quality. In turn it improves productivity of an organization. Hence, this study of EQ leadership on productivity aimed to explore EQ competences, such as, self-awareness, self-regulation, motivation, empathy and social skills on productivity of electronic industry in Malacca. This study is based on primary surbey data collected from assembled of 151 managerial and non-managerial employees.